Design and Psychometric of Smoking Cessation Instrument according to Precaution Adoption Process Model in Patients Hospitalized in Hospitals Affiliated to Medical University of Babol, Iran, during 2017 - Sahbaeiroy, Faezeh (Asian Journal of Pharmaceutics (AJP), 2018)
Background and Objective: There is no standard questionnaire on smoking cessation in smokers according to precaution adoption process model (PAPM). Therefore, the present study aimed to design and psychometrically evaluate a smoking cessation instrument in patients hospitalized in Babol, Iran, according to PAPM. Materials and Methods: This was a cross-sectional descriptive and instrument validation study. In this study, 470 smokers hospitalized in hospitals affiliated to the Medical University of Babol, Iran, were selected based on the available sampling method. Those who were highly dependent on nicotine were selected. The designed questionnaire was examined in terms of face validity, content validity, construct validity, and internal consistency. The reliability of the questionnaire was examined using Cronbach’s alpha and internal consistency. Results: Most of the people were with moderate dependence on nicotine (86%) at the fourth level (28.9%) of the pattern. The results of content validity showed content validity ratio of 0.83 and content validity index of 0.98. Seven factors were extracted from exploratory factor analysis. The results of exploratory factor analysis according to Kaiser-Meyer-Olkin measure and Bartlett test were 0.93 and 1124.63, respectively. The results of confirmatory factor analysis of instruments for 470 subjects were extracted with X2 and degree of freedom of 2.86, mean of error square of 0.06, goodness of fit index of 0.9, and adaptive goodness of fit of 0.9 Cronbach’s alpha (0.93) and correlation (0.99) confirmed the reliability of instrument in test–retest method. Conclusion: The findings showed that smoking cessation instrument based on PAPM has acceptable reliability and validity to determine the behavior of smoking in smoker men and can be used in studies on change in behavior and designing intervention programs to stop smoking.